Air data fault detection and isolation for small UAS using integrity monitoring framework. Issue 3 (6th September 2021) - Sun, Kerry; Gebre‐Egziabher, Demoz
Abstract: A Fault Detection and Isolation (FDI) algorithm is developed to protect against Water‐Blockage (WB) pitot tube failure in the safety‐critical Air Data System (ADS) used on small Unmanned Aircraft Systems (UAS). The algorithm utilizes two identical Synthetic Air Data Systems (SADS) as the basis for state estimation. Each SADS works independently with a pitot tube while sharing an IMU and GNSS receiver. The fault detection is designed using the integrity monitoring framework, and the isolation is obtained via independent fault detection channels. The ADS requirements are established, and the WB failure mode is analyzed based on real faulty air data. A new residual‐based test statistic is introduced, and the link among the test statistic, observability matrix, and Minimal Detectable Error (MDE) are examined. Finally, a flight data set with a known water‐blockage fault signature is used to assess the algorithm's performance in terms of the air data protection levels and alert limits.